A review of the tribe Podagrionini Ashmead, 1904 (Chalcidoidea: Torymidae) of the fauna of Russia and adjacent countries, with descriptions of two new species - S.V. Tyulina; G. Delvare (Кавказский энтомологический бюллетень, 2024)
Species of the tribe Podagrionini Ashmead, 1904 of the subfamily Podagrioninae Ashmead, 1904 (Hymenoptera: Torymidae) are reviewed. Four species from the Mediterranean Basin, Iridophaga lichtensteini (Picard, 1933), comb. rev., I. korsakowi (Picard, 1936), comb. rev., I. eremiaphilae (Doğanlar et Doğanlar, 2008), comb. n. and I. konyaensis (Doğanlar et Doğanlar, 2008), comb. n., are transferred from Podagrionella Girault, 1913 to Iridophaga Picard, 1933. Iridophagoides petiolatus Erdös, 1964, comb. rev. and I. tatianae Bouček, 1976, comb. rev. are transferred back to the genus Iridophagoides Erdös, 1964 from Podagrionella. Two new species, Podagrion kondarensis Tyulina, sp. n. from Russia and Tajikistan and Podagrion murgabensis Tyulina, sp. n. from Turkmenistan and Tajikistan, are described and illustrated. The female of P. libycum Masi, 1929 is described and illustrated for the frst time. New distribution records are reported: Iridophagoides tatianae in Armenia and Azerbaijan; Podagrion gibbum Bernard, 1938 in Russia, Armenia, Azerbaijan, Kazakhstan, Turkmenistan, Uzbekistan, Tajikistan and Kyrgyzstan; P. libycum Masi, 1929 in Russia, Turkmenistan and Tajikistan; P. minus Strand, 1911 in Armenia and Kazakhstan; P. pachymerum (Walker, 1833) in Abkhazia and Tajikistan; P. splendens Spinola, 1811 in Kazakhstan, Turkmenistan, Tajikistan and Mongolia. An identifcation key to females of the species of Podagrionini of the fauna of Russia and adjacent countries is provided.